Hepatic tumor or giant liver fascciola?: case report - Aguilar-Urbina, Edi William (2021)
Hepatic Fasciola is a frequent disease in the Peruvian highlands. We present a case of hepatic Fasciola from the Andean zone of La Libertad, with symptoms of several months of evolution with pain in the right hypochondrium, jaundice and coluria. An abdominal CT scan was performed, demonstrating a liver mass probable neoplasm, and was referred to the Institute of Neoplastic Diseases. Laboratory tests were completed finding eosinophilia and variable increases in liver function tests. Fascioliasis was presented as a differential diagnosis and a Western Bloot examination was performed confirming its diagnosis. Treatment with 2 cycles of Triclabendazole was started, with a favorable clinical evolution.